Bioakumulasi merkuri pada hepar tikus putih (Rattus norvegicus L.) dengan perlakuan kerang darah (Anadara granosa L.) tercemar merkuri - ABA, La ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Mercury is one of heavy metals founded in great number in waters as a waste resulting of industrial activities and mining especially gold mining. Mercury has a toxicity and high bioaccumulation potential in organs, especially in liver as target organ. Based on the issue, this research is conducted to analyze mercury bioaccumulation in the liver, SGPT and SGOT level as well as hepatocytes observations. In this experiment, it was used 2 months aged of male rat (Rattus norvegicus L.) with 150 gram weight. Animals model were divided into 4 groups with 3 replications, the control and 3 treatment groups with the variation interval. The control group (K) was animals fed with pellets only, whereas the treatment groups were fed with pellets by a mixture of bivalves contaminated mercury with ratio of 3: 1. Those variations were done every day, twice a day and once every three days for one month. Parameters include the of observation of hepatic mercury levels, SGPT and SGOT level as well as the structur of hepatocytes of rat. Hepatic mercury level, SGPT and SGOT levels are analyzed statistically by one way ANOVA test (α = 0.05) and than difference between one group with another group analyzed by Duncan's Multiple Range Test = DMRT. The qualitative data of hepatocytes condition of the rat was analyzed descriptively. The result showed that rats fed with mercury contaminated bivalves resulted mercury bioaccumulation in the liver with mercury level of PI, PII, PII were 21.37 ppb, 17.05 ppb and 8.25 ppb respectively. Whereas, the mercury content in the control group (K), which was only fed with pellets, does not detect at the detection limit of 0.62 ppb. Similarly, the SGPT level of PI, PII, PIII were 59.30 UI/ L, 43, 60 UI/L and 41.30 UI/L respectively. While, the treatment groups were resulted damage of hepatocytes. Keywords: mercury bioaccumulation, SGPT level, SGOT, Anadara granosa L., rat (Rattus norvegicus L.)